Numerical simulation of storm surges due to Typhoon Glenda (Rammasun), Basyang (Conson), and Milenyo (Xangsane) along the coastal barangays of Hagonoy, Bulacan - Leonardo, Marco Vino S.
The numerical simulation of storm surge from severe typhoons is a challenge for the government for the surge hazard mapping, disaster risk mitigation and emergency planning and evacuation schemes and measures. To minimize the loss of lives and properties, a necessity for practical measurements and real-time estimates and updates is an obligation of government and operational weather centers here in the Philippines. There is no attempt in modeling the storm surge along coastal areas of Bulacan especially along coastal barangays in Hagonoy. Also, the population along the coastal communities in Hagonoy in Bulacan is dense making it one of the most populated provinces not only in Region 3, but also in the Philippines. In addition for this, the primary livelihood for the people in the area is aquaculture. Therefore, the risk for coastal vulnerability is high because of the lives and livelihood at stake. To resolve these problems, the present study uses Advance Circulation Model (ADCIRC) to assess surge along the coast of Hagonoy, Bulacan for the Typhoon Rammasun (Glenda), Typhoon Conson (Basyang) and Typhoon Xangsane (Milenyo). Tide gauge data are available from National Mapping and Resource Information Authority (NAMRIA) to evaluate the skill of the model. The model data and tide gauge data are then computed. Residuals are expected since the gauge from NAMRIA measured the total water level while the model only computed the storm tide and did not account the wave action. The study also signifies the shallow beach slope and the shape of coastline have direct relationship in the storm surge occurrence. This research highlights that storm surge modeling should comprise an integral part in improvement in the evaluation of coastal hazards for government operations.